2019
DOI: 10.36740/wlek201906102
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors of Dysmenorrhea in Young Women

Abstract: The Aim: To evaluate risk factors for dysmenorrhea in women of reproductive age and to review its characteristics. Material and Methods: A questionnaire was conducted among 354 women followed by a statistical analysis of the gathered data. Results: Among the interviewed women 84.2 % suffer from painful menstruations. Women under 25 years of age are more likely to experience pain, which reduces with age. Dysmenorrhea is more common among women whose menstrual cycles are irregular (92.5%) with a number of bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
1
8
2
1
Order By: Relevance
“…The current study revealed a relatively high prevalence of primary dysmenorrhea among Lebanese university students. This finding is in line with several cross-sectional studies conducted in different countries including 89.6% in Lebanon [ 7 ], 84.2% in Lithuania [ 41 ], 88% in Australia [ 42 ], 85.1% in Palestine [ 43 ], 83.6% in Northern Ghana [ 44 ], and 84.1% in Italy [ 45 ]. This indicates that PD is a common public health issue that should be addressed appropriately.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current study revealed a relatively high prevalence of primary dysmenorrhea among Lebanese university students. This finding is in line with several cross-sectional studies conducted in different countries including 89.6% in Lebanon [ 7 ], 84.2% in Lithuania [ 41 ], 88% in Australia [ 42 ], 85.1% in Palestine [ 43 ], 83.6% in Northern Ghana [ 44 ], and 84.1% in Italy [ 45 ]. This indicates that PD is a common public health issue that should be addressed appropriately.…”
Section: Discussionsupporting
confidence: 89%
“…Heavy menstrual blood flow might be considered a risk factor and a consequence of PD and this could be explained by the fact that PGs can disturb the homeostatic mechanism of the endometrium, hence increasing the blood flow [ 52 ]. Studies have also shown that women younger than 25 years are more likely to have PD, and the prevalence of dysmenorrhea falls with increasing age [ 41 , 53 ]. However, although the prevalence in the current study was higher among females younger than 25 years, interestingly no statistical significance was detected among different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…In recreational athletes, the 3-month sample prevalence and incidence rate of lymphoproliferative disorders and anovulatory menstrual cycles is 48% and 79%, respectively ( De Souza, 2003 ). The above-mentioned studies, therefore, support the assertion that female athletes who have regular monthly cycles can, nevertheless, have problems such as chronic anovulatory cycles or a defect luteal phase ( Vilšinskaite et al, 2019 ).…”
Section: Discussionmentioning
confidence: 55%
“…Kondisi ini dapat menyebabkan kontraksi miometrium yang dapat menimbulkan iskemia miometrium dan hiperkontraktivitas uterus. Kondisi inilah yang dapat menimbulkan nyeri dismenore (Vilšinskaitė et al, 2019).…”
Section: Pendahuluanunclassified